Efeitos cardiovasculares e metabólicos em animais submetidos à dessincronização circadiana - Oliveira, Isis Gabrielli Barbieri de (2017)
The presence of circadian rhythms in organisms is a biological event, indispensable to the process of adaptation to the environment and fundamental for the survival of the species. The loss of the phase relationship between the biological rhythms and the behavior leads impairment of the body function. Thus, the aim of this study was to evaluate the effects of the forced locomotor activity desynchronization on the cardiovascular and metabolic parameters. Male Wistar rats, aged approximately 60 days, were distributed into two experimental groups: control group (CTR) submitted to the light/dark cycle (LD) of 24h-T24 (n=12) and desynchronized group (DSC) submitted to the LD cycle of 22h -T22 (n = 18) for eight weeks. Records of the locomotor activity were made daily to both groups. Food ingestion, water intake and body weight were monitored weekly. Following of this period the animals were allocated into two experimental protocols. In the first protocol the CTR and DSC animals were submitted to records of mean arterial pressure (MAP) and heart rate (HR), as well as pharmacological tests of baroreceptor reflex function and cardiac autonomic control, such as intrinsic pacemaker heart rate (IPHR); vagal and sympathetic effects and sympathetic-vagal index (SVI). In the second protocol, CTR and DSC animals were fasted for at least 12 hours, anesthetized and euthanized by decapitation to collect blood, liver and adrenal glands for posterior analysis of plasma glucose, triglycerides, total cholesterol, VLDL, HDL, LDL; the expression of proteins involved in the insulin signaling cascade (IR-β; IRS-2; PI3K; AKT), the gluconeogenic enzyme - PEPCK, SOD-1 and CAT; and morphometry. Although there was no significant difference in feed and water intake between groups, a higher weight gain of DSC animals was observed from week 7 onwards. In relation to the pattern of locomotor activity, DSC animals presented lower levels on total locomotor activity with a predominance of its activity during the light phase of the LD cycle. Although we did not observe significant alterations in the basal MAP and HR levels between the groups, the DSC animals showed reduction of the baroreflex sensitivity by the bradycardic index, as well as a higher cardiac sympathetic effect. No differences were observed between the groups for the other parameters of cardiac autonomic control. Regarding the biochemical parameters, we observed in the DSC animals, a reduction in HDL cholesterol associated with an increase in LDL cholesterol, which promoted a high index of Castelli I and II, compared to the CTR. There were no differences in plasma levels of glucose, triglycerides, total cholesterol and VLDL. DSC animals also showed an increase in weight and in the total area of the adrenal glands. In addition, we observed decreased IRβ, IRS-2, PI3-K and Akt proteins, as well as increased expression of the gluconeogenic enzyme PEPCK in DSC animals, suggesting hepatic insulin resistance. Finally, we observed a reduction in the expression of the SOD-1 and CAT enzymes in the DSC animals in relation to the CTR animals. Summarizing, our results suggest that a 22h symmetrical photoperiod (T-22) promotes lower baroreflex sensitivityand increased sympathetic effect on the heart. In addition, metabolic disorders such as hepatic insulin resistance and increased hepatic oxidative stress were observed in the desynchronized rats.